A Survey on Transmission Schemes on Large-Scale Internet of Things with Nonorthogonal Multiple Access. (28th September 2021) - Zhou, Wenyu; Zhao, Rui; Zhu, Fusheng; Lai, Lijia; Li, Xutao
Abstract : This paper performs a comprehensive survey on transmission schemes for the large-scale Internet of things (IoT) networks with nonorthogonal multiple access (NOMA). By solving the interference among users, NOMA can significantly improve the frequency reuse efficiency and support multiple users to use the same frequency resources. It is considered to be one of the most effective technologies for the next-generation wireless communication. However, there are still many challenges on the transmission schemes for the large-scale NOMA system, including the short-data packet transmission, active user detection, channel estimation, and data detection. In order to meet these challenges, this paper first reviews the short-packet transmission in the large-scale NOMA systems and then reviews the active user detection and channel estimation technologies of the considered systems.